Límites a la modificación de contratos en la ley 9/2017 de 8 de noviembre de contratos del sector público. análisis de la transposición al ordenamiento español de la directiva 2014/24/UE - Cristina Clementina Arenas Alegría (Revista Vasca de Administración Pública)
In the framework of the execution of a public contract some specific causes can change its nature and therefore make necessary some amendments. The contrast that occurs in those cases between the public interest aimed at the maintenance of the contract although it involves an amendment and the premature termination of it due to the inability to perform the agreed service, has provoked that national and european legislators priorize in some occasiones for one or the other. The Spanish legislation up until the passing of the Sustainable Economy Act was very timid regading the control of amendments. Once Directives from 2014 about public procurement were enacted it was neccesary their transposition by following the line that understands that the modifications should be addressed as exceptional and justified with the purpose of not undermining the competitive nature of bidding. We try to analyze the transposition of the Directive from 2014 by the Public Sector Contracts Act.